PENGARUH KECERDASAN EMOSIONAL, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA DINAS BINA MARGA PROPINSI SULAWESI TENGAH - Purady, Rudiyanto (Katalogis, 2016)
This research aims to explore and analyze simultaneous and partial impacts of emotional quotient, work environment, and work culture on employee performance in Bina Marga Agency of Central Sulawesi. It involves 136 employees as respondennts and applies multiple linear regressions with explanatory method of analysis. The results highlight that emotional quotient, work environment, and work culture simultaneously and partially have significant influence on employees’ performance in Bina Marga Agency of Centra Sulawesi